Inovasi Teknologi Pupuk Organik Cair Dari Limbah Pada Berbagai Varietas Rumput Gajah: Studi Kandungan Nutrisi Di Lahan Eks-Perkebunan Kelapa Sawit : English - Mariam, Mariam; A N Insani (Jurnal Ternak, 2025)
This study aims to evaluate the effects of liquid organic fertilizer (LOF) derived from waste materials on soil quality and the nutritional content of Napier grass grown on former oil palm plantation land. The research is motivated by the need for sustainable and environmentally friendly fertilization alternatives to improve degraded soil fertility and enhance forage quality for livestock. The methodology included chemical analysis of soil, assessment of LOF quality based on the Ministry of Agriculture standards, and evaluation of nutritional parameters in three Napier grass varieties (Bio Vit, Bio Nutrient, and Bio Grass) under four treatment levels of LOF (P0–P3). Parameters measured comprised soil and LOF pH, nitrogen (N), phosphorus (P), and potassium (K) content, as well as crude protein, crude fiber, neutral detergent fiber (NDF), and acid detergent fiber (ADF) levels in the grasses. The results indicated that the study site soil was acidic (pH 4.5) with low to very low N, P, and K levels. The applied LOF had a pH of 5 and met the required standards for N and K content but failed to meet the minimum requirement for P. Application of LOF significantly increased crude protein and reduced crude fiber, NDF, and ADF content in Napier grass, with the Bio Vit variety showing the most favorable response. Bio Nutrient exhibited stable improvement trends, while Bio Grass showed more variable outcomes, particularly in ADF levels. In conclusion, LOF application can enhance soil fertility and forage quality, particularly in marginal soils. The Bio Vit variety is recommended for its high responsiveness to LOF in improving livestock feed value.